Toroidal mode number determination of ELM associated phenomena on ASDEX Upgrade. (3rd November 2016) - Mink, Felician; Wolfrum, Elisabeth; Maraschek, Marc; Zohm, Hartmut; Horváth, László; Laggner, Florian M; Manz, Peter; Viezzer, Eleonora; Stroth, Ulrich
Abstract: In highly confined tokamak plasmas periodically appearing edge localized modes (ELMs) are accompanied by mode-like magnetohydrodynamic (MHD) activities with defined toroidal mode numbers. Here the method of determining toroidal mode numbers n on the ASDEX Upgrade tokamak with a toroidally spread magnetic pick-up coil array is reviewed and improved by taking into account intrinsic coil phases. ELM synchronization is used to characterize inter-ELM MHD activity and their development during the ELM cycle in terms of their mode numbers. The mode number development is correlated with the development of the pedestal parameters which shows that the inter-ELM modes cause transport across the pedestal. An estimation of the position of the modes is done via a comparison between the mode velocities and the plasma rotation profile at the edge. Results show that during the ELM cycle MHD modes appear at several positions in the strong gradient region with clearly defined toroidal structures in the range of n   =  1–10. These structures of inter-ELM modes are preserved during the ELM crash where also a strong n   =  0 phenomenon occurs.